Complete Hydatidiform Mole with a Coexisting Viable Male Fetus Detected by Cell-Free DNA - Mackenzie Lemieux; Lauren Kus; Kali Stewart; Mai He; Jackson Rowe; Matthew Brady; Katherine Bligard; Megan Lawlor; Jeannie Kelly (Thieme Medical Publishers, Inc., 2023)
Complete hydatidiform mole with coexisting fetus (CHMCF) is rare, and diagnosis is challenging due to limited data. Here, we present the case of a patient with noninvasive prenatal test (NIPT) resulting in "likely molar pregnancy" in the second trimester. Subsequent ultrasound confirmed a cystic appearing portion of the placenta. At 22 weeks, the patient delivered a demised fetus and two placentas. Pathology was consistent with CHMCF. This case is the first to show primary detection of a CHMCF with single-nucleotide polymorphism (SNP)-based NIPT prior to ultrasound identification. Our case suggests the use of SNP-based NIPT as an alternative noninvasive method to guide shared decision-making and clinical management for patients with this diagnosis.